2016
DOI: 10.1007/s00467-015-3283-3
|View full text |Cite
|
Sign up to set email alerts
|

Body composition monitoring-derived urea distribution volume in children on chronic hemodialysis

Abstract: In our pediatric HD patients the V measured by BCM was in agreement with that calculated using the Morgenstern equation, which is the only equation which has been validated to date in children on dialysis. Online determination of Kt/V using a BCM-derived V largely agreed with that calculated by the Daugirdas equation. We therefore conclude that the former approach is suitable for frequent online assessment of dialytic small solute clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Ionic dialysance (K OCM ), reflecting urea and small solute clearance, is ordinarily used to quantify dialysis efficiency from periodic measurements (every 30 minutes) and to provide an integrated dialysis performance (K OCM ) throughout the complete dialysis session 28 . Overall ionic clearance (K OCM ) is then used as a surrogate of effective urea clearance both in hemodialysis and ol‐HDF expressed either in total clearance over the session (K OCM times treatment time ( t d ) in L/session) or in fractional clearance (K OCM t d /V) where V (urea volume or total body water) is referring to an anthropometric value derived from the Watson formula 27,29‐31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic dialysance (K OCM ), reflecting urea and small solute clearance, is ordinarily used to quantify dialysis efficiency from periodic measurements (every 30 minutes) and to provide an integrated dialysis performance (K OCM ) throughout the complete dialysis session 28 . Overall ionic clearance (K OCM ) is then used as a surrogate of effective urea clearance both in hemodialysis and ol‐HDF expressed either in total clearance over the session (K OCM times treatment time ( t d ) in L/session) or in fractional clearance (K OCM t d /V) where V (urea volume or total body water) is referring to an anthropometric value derived from the Watson formula 27,29‐31 …”
Section: Discussionmentioning
confidence: 99%
“…28 Overall ionic clearance (K OCM ) is then used as a surrogate of effective urea clearance both in hemodialysis and ol-HDF expressed either in total clearance over the session (K OCM times treatment time (t d ) in L/session) or in fractional clearance (K OCM t d /V) where V (urea volume or total body water) is referring to an anthropometric value derived from the Watson formula. 27,[29][30][31] The originality of our work was to develop a simple sodium Flux model relying on K OCM values to compute ionic (sodium equivalent) dialysance, and then to estimate the net sodium mass removal using plasma and dialysate sodium concentrations estimated from conductivity measurements. Ionic mass balance has been proposed by different authors to guide dialysate sodium prescription to implement isonatremic dialysis or to prevent sodium patient load.…”
Section: Discussionmentioning
confidence: 99%
“…24,59 The evidence of association between BCM assessment and improved patient outcomes is mixed. The Canadian Agency for Drugs and Technologies in Health (CADTH)'s rapid-response report, published in 2015, 53 identified two randomised controlled trials (RCTs) of 131 and 189 participants, respectively 60,61 and one observational study of 110 participants, which assessed the use of the BCM in people receiving HD.…”
Section: Body Composition Monitormentioning
confidence: 99%
“…24,[72][73][74] Appendix 2 presents the characteristics of these studies. In the list of non-randomised studies that were not deemed suitable for inclusion based on the above criteria, no UK-based studies, studies that included any of the specified devices (other than the BCM) or studies reporting relevant outcomes not otherwise described in the report were identified.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation